The Predominant Elements for Strategic CSR Implementation in SMEs - Gunawan, Sandy; Syarief, Rizal; Nurhayati, Popong; Asnawi, Yudha Heryawan; Joewono, Handito Hadi (International Research Journal of Business Studies, 2022)
Research on strategic Corporate Social Responsibility (CSR) in small and medium-sized enterprises (SMEs) is still not many in number, particularly, in developing countries. Although SMEs play an important role in economic development, this sector has received less attention in research on its competitiveness through social responsibility. According to previous literature, SMEs have unconsciously practiced social responsibility but have not been integrated in their strategy. The same condition has also occurred to SMEs in Badung district, Bali, where they practice social responsibility in running their business as an embodiment of a philosophy based on religious teachings. However, this type of CSR has not yet made a positive contribution to their competitiveness. This study attempts to answer what elements are required to obtain CSR as strategy. Interpretive Structural Modeling methodology was implemented to the SMEs located in Badung Regency, Bali . The study finds that the integration of strategic CSR into SMEs’ strategy was focused on new paradigm improve SMEs’ competitiveness. This new way of thinking can be achieved by intensively socializing the benefits of strategic CSR through education, relevant policy and collaboration between related stakeholders.